Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1016/s0960-9822(01)00142-7
|View full text |Cite
|
Sign up to set email alerts
|

CDC-42 controls early cell polarity and spindle orientation in C. elegans

Abstract: Our results show that CDC-42 acts in concert with the PAR proteins to control the polarity of the C. elegans embryo, and provide evidence that the interaction of CDC-42 and the PAR-3/PAR-6/PKC-3 complex has been evolutionarily conserved as a functional unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
188
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 28 publications
(13 reference statements)
11
188
0
Order By: Relevance
“…The essential role of Cdc42 in the apical-basal polarity of the telencephalic NE is similar to its important functions in regulating PAR protein localization and early cell polarity in C. elegans (17,18). Cdc42 also sequentially directs Par-6, aPKC, and Lgl to establish the epithelial polarity during Drosophila embryogenesis (19).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The essential role of Cdc42 in the apical-basal polarity of the telencephalic NE is similar to its important functions in regulating PAR protein localization and early cell polarity in C. elegans (17,18). Cdc42 also sequentially directs Par-6, aPKC, and Lgl to establish the epithelial polarity during Drosophila embryogenesis (19).…”
Section: Discussionmentioning
confidence: 87%
“…First, Cdc42 regulates PAR protein localization and controls the anteriorposterior polarity in Caenorhabditis elegans embryos (17,18). Secondly, Cdc42 sequentially directs Par-6, aPKC, and Lgl to establish the epithelial polarity in Drosophila (19).…”
mentioning
confidence: 99%
“…The current biochemical model depicts that upon activation of a variety of cell surface receptors, Cdc42 can be activated to recognize specific downstream effectors to regulate multiple cell functions including actin cytoskeleton reorganization (Hall, 1998), directional migration, gene expression, and cell cycle S-phase progression (Kjoller and Hall, 1999;Ridley, 2001;Etienne-Manneville and Hall, 2002). Although genetic evidence for the related cell functions of Cdc42 is particularly strong in lower eukaryotes including Saccharomyces cerevisiae and Caenorhabditis elegans (Johnson and Pringle, 1990;Gotta et al, 2001;Kay and Hunter, 2001), genetic support for these roles of Cdc42 in mammalian cells is limited, in part because conventional gene targeting of Cdc42 leads to early embryonic lethality (Chen et al, 2000), and most published literature on mammalian Cdc42 cell function are derived by using dominant negative or constitutively active mutant expression approaches in clonal cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous work demonstrated that while removing both copies of par-2 leads to the mislocalization of the anterior PARs to the posterior of the embryo, and thus to defects in polarity and embryonic lethality, reducing by half the amounts of PAR-6 in a par-2 mutant background is sufficient to restore viability (Watts et al 1996) (supplemental Figure 1 at http:/ /www.genetics.org/supplemental/). Similarly, disruption by RNA interference (RNAi) (Fire et al 1998) of cdc-42, a regulator of the anterior PAR activity, in a par-2 mutant also restores viability (Gotta et al 2001). These results indicate that genes that are required to regulate the levels, the localization, and/or the activity of anterior PAR components can be identified on the basis of their ability to restore viability in a par-2 mutant background.…”
mentioning
confidence: 99%